THE INFLUENCE OF BRAND AMBASSADOR, BRAND IMAGE AND BRAND AWARENESS ON PURCHASE DECISIONS CONSUMERS OF SHOPEE MARKETPLACE - Erliana, Fadilla Putri; Nurani (Universitas Tulungagung, 2025)
Globalization and the development of science and technology have changed the lifestyle and needs of people around the world. Technology, especially information and communication via the internet, facilitates human activities. Social media plays an important role in education, entertainment, and business. In Indonesia, many people have switched from conventional shopping to online shopping, especially in the Marketplace. Reviews on the internet also influence purchasing decisions. This study analyzes the influence of Brand Ambassador, Brand Image, and Brand Awareness on consumer purchasing decisions in the Shopee Marketplace. The object of this study is Shopee Marketplace consumers related to Brand Ambassador, Brand Image, Brand Awareness, and purchasing decisions. This study uses a quantitative approach, the type of research is positivism philosophy, the sample in this study uses the purposive sampling method and data collection using the questionnaire method, literature study, and observation. The results show that all variables have a significant effect on purchasing decisions, different from previous studies